PEMETAAN TREN PENELITIAN DALAM PENDIDIKAN DESAIN GRAFIS: ANALISIS BIBLIOGRAFI TAHUN 2004–2024 - Muhaemin, Muhammad (Universitas Negeri Makassar, 2025)
This study aims to map global research trends in the field of graphic design education over the past two decades (2004–2024) using a bibliometric approach based on Scopus data. A total of 538 documents were analyzed, focusing on keyword frequency, author collaboration networks, and citation distribution across countries. Visualization was conducted using VOSviewer and Biblioshiny to identify thematic clusters and the most productive authors. The analysis revealed that topics such as graphic design, design education, and visual communication design were the most dominant keywords. Authors such as Maria Cutumisu, Elmarie Costandius, and Asrul Huda ranked among the most productive contributors, while China, the United States, and Indonesia emerged as the top-cited countries. These findings reflect the growing role of technology, artificial intelligence, and pedagogical innovation in design education. This study provides strategic insights for academics and policymakers to foster international collaboration and adapt design curricula in response to global dynamics.